Imperfect nestling-mimicry attracts high-quality females in the Asian barn swallow. Issue 6 (2nd November 2018) - Hasegawa, Masaru; Arai, Emi
Abstract : The sensory trap hypothesis predicts that male signals mimic stimuli to which females respond in other contexts, yet these signals may not elicit equivalent responses from all females. Female barn swallows Hirundo rustica are attracted to male enticement calls, particularly high-pitched ones that resemble the food-begging calls of nestlings to a greater extent. However, male enticement calls are still distinguishable from nestling food-begging calls, denoting "imperfect mimicry". It remains unknown why perfect mimicry is prevented given that nestling-like calls effectively attract females. Here, using Asian subspecies ( H. r. gutturalis ), we examined female preference for male enticement calls to nestling food-begging calls during the mating period in relation to the ornamentation of her previous mate and trial date, a proxy of female arrival date, in this experiment with the expectation that females vary their response depending on these variables. We found that female reaction to the playback of male enticement calls, relative to the playback of nestling food-begging calls, increased with increasing plumage coloration of her previous mate, and decreased with increasing trial date (and hence late arrival). This observation is predictable, because colorful males emit lower-pitched, i.e. less nestling-like, enticement calls, and because early-arriving females, which are more experienced females, would have higher discriminability than others. Imperfect mimicry to nestling food-begging calls would attract relatively high-quality females, and thus males should not emit enticement calls that closely resemble nestling food-begging calls except when high-quality females are not available.